Generalized molluscum contagiosum in an HIV patient treated with diphencyprone - Leena Chularojanamontri (2018)
Background: Diphencyprone is a universal contact immunotherapy. The mechanism of action is based on an induction of the delayed-type hypersensitivity. Diphencyprone has been used in various forms for treatments of recalcitrant and facial warts, and alopecia areata. However, this treatment modality has not been generally used in immunocompromised patients. Main observation: The present report demonstrated the efficacy of diphencyprone immunotherapy on the treatment of generalized molluscum contagiosum in a human immunodeficiency virus (HIV)-infected patient. Minimal and transient side effects including pruritus, postinflammatory hyperpigmentation and irritation were noted. Conclusion: Diphencyprone contact immunotherapy appears to be a possible alternative treatment of widespread molluscum contagiosum in immunocompromised patients.